If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 14 = -9x + -16 Reorder the terms: 14 + 6x = -9x + -16 Reorder the terms: 14 + 6x = -16 + -9x Solving 14 + 6x = -16 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 14 + 6x + 9x = -16 + -9x + 9x Combine like terms: 6x + 9x = 15x 14 + 15x = -16 + -9x + 9x Combine like terms: -9x + 9x = 0 14 + 15x = -16 + 0 14 + 15x = -16 Add '-14' to each side of the equation. 14 + -14 + 15x = -16 + -14 Combine like terms: 14 + -14 = 0 0 + 15x = -16 + -14 15x = -16 + -14 Combine like terms: -16 + -14 = -30 15x = -30 Divide each side by '15'. x = -2 Simplifying x = -2
| 5+m=4x+3 | | 2(4+9w)=26w | | (w+2)(2w-1)=0 | | 2*8+3*-9= | | 3.45*4-8.18= | | 8m-5=(3m+5) | | 3.45(4)-8.18(1)= | | 3+3*6+2=-17 | | 500*98+x*0=(500+x)*30 | | 6n+3-5=-1 | | 6y+814=1186 | | cos(20)=(9/x) | | 32/-7 | | 4(1/4) | | 3x+10y=-15 | | F^2-22f+72=0 | | (5-8w)(5+8w)= | | 12-9y=-5 | | -7x+6-9=29 | | -4+3=-12+17x | | 3z/10-5=8 | | 5(2b-3)=3(b+9) | | 12(12n)+n-3=396 | | 1/8-X/7=3/56 | | F^2-22f=72 | | -4(1-7z)=-29 | | 5x-2/3=-49/10 | | 15x^4-15x^3=0 | | Z/7-2=6 | | f(x)=x^4+32 | | 8(p-a)-6=2(ap-5) | | 6x+7y(2-3y)=-21 |